The Use of Visual Media in Social Studies Learning to Overcome Students' Difficulties in Understanding the Geographical Location of ASEAN Countries in Grade VI Elementary School Students - Siti Arofah; Oktafia Fitriani; Febriyah Izzatur Rif'ah; Ananda Nailatus Sa'adah; Risma Nisa Khoirina; Priyono Tri Febrianto (AR-RIAYAH: Jurnal Pendidikan Dasar, 2026)
Social Studies learning regarding the geographical location of ASEAN in grade VI is often constrained by extensive and abstract material, making it difficult for students to visualize interregional connectivity spatially. This research aims to analyze in detail visual media innovation trends from 2021 to 2025 across four focuses: publication patterns, media-learning outcome matrices, pedagogical implications, and research gaps. Utilizing the Systematic Literature Review (SLR) method based on PRISMA 2020 guidelines, 52 studies were selected from 300 articles on Google Scholar for in-depth analysis. The findings reveal these four trends and highlight the limitations of static visual media compared to interactive media in explaining complex geographical dynamics. The primary contribution of this research is the synthesis of visual media effectiveness in overcoming cognitive barriers for sixth-grade students. Furthermore, the results of this analysis serve as a practical guide for educators in selecting the most relevant visual tools to enhance the quality of Social Studies learning. By integrating appropriate media, spatial obstacles can be minimized, ensuring that students' understanding of ASEAN regional connectivity becomes more comprehensive and meaningful.